2022
DOI: 10.3390/ani13010020
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Levels of Fish Meal and Methionine in Diets for Juvenile Litopenaeus vannamei to Support Maximum Growth Performance with Economic Efficiency

Abstract: This work investigated the optimal levels of fish meal (FML) and dietary methionine (Met) required for maximum growth performance of juvenile Litopenaeus vannamei with economic efficiency. Four sets of diets were prepared to contain 0.00, 6.00, 12.00 and 18.00% FML. Each set was supplemented with DL-methionyl-DL-methionine (DL-Met-Met) to result in a total dietary Met (Met + Cys) content of 0.58 (1.05), 0.69 (1.16), and 0.82% (1.29%), on a fed basis. Shrimp of 1.00 ± 0.08 g were stocked in 60 outdoor tanks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
3
9
0
Order By: Relevance
“…This supports the growth theory for the panel of nations that produce fisheries. This result confirms the critical finding of McKinley ( 2023), Nunes andMasagounder (2023), andStarkweather et al (2023), who discovered a favorable and inelastic influence of economic expansion on the development of the fisheries sector. The EU region's fisheries sector may achieve sustained growth by creating the right circumstances for an economically viable and competitive market (Magazzino, 2016a).…”
Section: Panel Estimation Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This supports the growth theory for the panel of nations that produce fisheries. This result confirms the critical finding of McKinley ( 2023), Nunes andMasagounder (2023), andStarkweather et al (2023), who discovered a favorable and inelastic influence of economic expansion on the development of the fisheries sector. The EU region's fisheries sector may achieve sustained growth by creating the right circumstances for an economically viable and competitive market (Magazzino, 2016a).…”
Section: Panel Estimation Resultssupporting
confidence: 90%
“…This finding supports the efficacy of fisheries policy in promoting economic expansion in higher‐producing nations. The efficiency of the economic performance, according to McKinley (2023), Nunes and Masagounder (2023), and Starkweather et al (2023), is what drives the fisheries sector to seek sustainable growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the feed industry, especially the widespread use of fish meal (FM) and fish oil (FO), has provided shrimp farming with feeds of consistent quality and convenient availability, which is one of the factors contributing to large‐scale shrimp farming and significant increase in production 5 . As the most costly component of shrimp feed, high‐quality protein sources such as FM provide the shrimp with required nutrients for fast and healthy growth 6 . The average FM level in shrimp feed is relatively high, for example, it was nearly 27% in China in 2018 and a recent study reported that it could be decreased to 12% or less in global aquaculture 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…5 As the most costly component of shrimp feed, high-quality protein sources such as FM provide the shrimp with required nutrients for fast and healthy growth. 6 The average FM level in shrimp feed is relatively high, for example, it was nearly 27% in China in 2018 and a recent study reported that it could be decreased to 12% or less in global aquaculture. 7,8 Besides, the FM supply has been affected by climate change (El Nino phenomenon), overexploitation of fish stocks, and competitive use in other markets and shipping.…”
Section: Introductionmentioning
confidence: 99%